The use of technical assistance for administrative capacity building in the 2014-2020 period - Strathclyde Business School (Publications Office of the European Union, 2020)
This study aims to enhance the understanding of the planned and implemented use of Technical Assistance (TA) at the initiative of Member States during the 2014-2020 period. It provides a quantitative overview of TA budget for the EU28 as a whole, for groups of Member States and for categories of TA expenditure. It presents a detailed assessment of TA budget for selected OPs, analysing the thematic allocation of budget according to an original reclassification of expenditure. It provides examples of transferrable practices of use of TA resources for administrative capacity building, and the identification of internal and external factors influencing the effectiveness of capacity-building initiatives. The study finds that effective use of TA for administrative capacity building depends on the existence of well-founded, coherent and forward-looking strategies, and on good governance (based on leadership, coordination and stakeholder involvement) underpinned by a learning culture. Recommendations for 2021-2027 relate to: (a) the development of administrative capacity building roadmaps, with TA used for a wider set of capacity building activities; (b) support for the entire 'ecosystem' of ESIF management and implementation; (c) the development of learning strategies for administrative capacity building; and (d) coherent management of administrative capacity building at EU level, whereby the support provided for administrative capacity building through TA should be coordinated with wider public service administrative reforms.
10.2776/645717
Keywords: Graue Literatur; Technische Zusammenarbeit; Öffentliche Verwaltung; Regionalpolitik; Stadtentwicklung; EU-Staaten; technical cooperation; staff; personnel administration; operational programme; vocational training; operating cost; economic and social cohesion; administrative cooperation; administrative reform; fund (EU); organisational culture; European Structural and Investment Funds; EU Member State; case study